La France et la crise du Golfe 1990-1991 : analyse politico-économique d'un virage - Saul, Samir (Études internationales, 1995)
The article situates official French policy during the crisis in the general framework of its international relations. It was somewhat surprising to see a country close to Iraq join the coalition. The first part is a reminder that France was, after the United States, the most zealous of the coalition members, and that its stated objectives did not correspond to its real aims. The second part takes stock of Franco-Iraqi relations in order to assess their state in August 1990. Business dwindled after the 1970s and stagnation set in as a result of the war against Iran and the downturn in oil prices. On the eve of the crisis, relations were at a standstill while accords to settle arrears in payments went into effect. The third part puts Franco-Iraqi relations in the context of the general reorientation of the French economy. At the time of the Gulf crisis, France was turning the page on the era of megaprojects in developing countries and integrating more thoroughly in the developed economies. The article concludes that French policy during the crisis, a short-term political event, was in accord with economic changes occurring over the intermediate term, without being their direct consequence.